Structure-guided examination of the mechanogating mechanism of PIEZO2 - Taberner, Francisco J.; Prato, Vincenzo; Meyer, Irina; Schrenk-Siemens, Katrin; Heppenstall, Paul A.; Lechner, Stefan (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Piezo channels are mechanically activated ion channels that confer mechanosensitivity to a variety of different cell types. Piezos oligomerize as propeller-shaped homotrimers that are thought to locally curve the membrane into spherical domes that project into the cell. While several studies have identified domains and amino acids that control important properties such as ion permeability and selectivity as well as inactivation kinetics and voltage sensitivity, only little is known about intraprotein interactions that govern mechanosensitivity—the most unique feature of PIEZOs. Here we used site-directed mutagenesis and patch-clamp recordings to investigate the mechanogating mechanism of PIEZO2. We demonstrate that charged amino acids at the interface between the beam domain—i.e., a long a-helix that protrudes from the intracellular side of the “propeller” blade toward the inner vestibule of the channel—and the C-terminal domain (CTD) as well as hydrophobic interactions between the highly conserved Y2807 of the CTD and pore-lining helices are required to ensure normal mechanosensitivity of PIEZO2. Moreover, single-channel recordings indicate that a previously unrecognized intrinsically disordered domain located adjacent to the beam acts as a cytosolic plug that limits ion permeation possibly by clogging the inner vestibule of both PIEZO1 and PIEZO2. Thus, we have identified several intraprotein domain interfaces that control the mechanical activation of PIEZO1 and PIEZO2 and which might thus serve as promising targets for drugs that modulate the mechanosensitivity of Piezo channels.